1987
DOI: 10.1152/ajpregu.1987.253.2.r228
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte blood flow is decreased in obese Zucker rats

Abstract: Blood flow to five adipose tissue depots and five other organs was measured in unanesthetized free-moving obese and lean male Zucker rats using the radiolabeled microsphere technique. Cardiac output and blood pressure were also measured. Obese rats were significantly heavier and had larger fat depots characterized by more and larger adipocytes. Cardiac output and blood pressure were similar in lean and obese rats. Blood flow to adipose tissue was substantially reduced in all five depots of obese rats when expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
33
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 0 publications
10
33
0
Order By: Relevance
“…In rats, sympathetic denervation produces greater changes in retroperitoneal compared to epididymal fat depots (4). There are also differences in regional blood flow, which is greater in mesenteric than subcutaneous adipose tissue (32). If similar differences in innervation and blood flow to abdominal fat depots occur in humans, one can speculate that altered sympathetic activity may lead to specific regional accumulations of fat resulting in the subgroup differences we observed.…”
Section: Discussionmentioning
confidence: 70%
“…In rats, sympathetic denervation produces greater changes in retroperitoneal compared to epididymal fat depots (4). There are also differences in regional blood flow, which is greater in mesenteric than subcutaneous adipose tissue (32). If similar differences in innervation and blood flow to abdominal fat depots occur in humans, one can speculate that altered sympathetic activity may lead to specific regional accumulations of fat resulting in the subgroup differences we observed.…”
Section: Discussionmentioning
confidence: 70%
“…Nevertheless, there is no increase in cardiac output or blood flow to the adipose tissue, particularly to WAT [96][97][98]. Previous studies on animal models revealed lower levels of oxygen in WAT in obese mice when compared with lean mice [99].…”
Section: Hypoxia and Angiogenesismentioning
confidence: 98%
“…West et al [32] demonstrated that blood flow to adipose tissue, measured with radiolabeled microsphere, was reduced in Zucker obese rats. In humans, the levels of adipose tissue blood flow were measured with positron emission tomography using [ 15 O]-labeled water [33] and the 133 Xe washout method [34] and were lower in obese compared with non-obese subjects.…”
Section: Effect Of Adipocyte Hypertrophy On Adipose Tissue Blood Flowmentioning
confidence: 99%